Women's Political and Social Thought An Anthology - Smith, Hilda; Carroll, Berenice (Indiana University Press, 2000)
Women's Political and Social Thought: An Anthology is the first collection of source readings of women's important writings in political and social theory from ancient times to the twentieth century. It fills a major gap in materials available for teaching the history of political thought and opens paths for exploring the rich and diverse contributions of women as creators of theory. Not confined to works of feminist theory, this anthology makes available substantial selections from women's writings across the political spectrum and in varied forms, from epic poetry, fiction, drama, and autobiography to prose works on history, politics, religion, and philosophy. The twenty-five authors represented in the anthology include: the ancient Sumerian high priestess Enheduanna, Sappho of Lesbos, Diotima of Mantinea, Sei Shonagon, Catherine of Siena, Christine de Pizan, Margaret Cavendish, Sor Juana Ines de la Cruz, Mary Astell, Phillis Wheatley, Olympe de Gouges, Mary Wollstonecraft, Angelina and Sarah Grimké, Flora Tristan, Josephine Butler, Vera Figner, E. Pauline Johnson (Tekahionwake), Ida B. Wells-Barnett, Jane Addams, Rokeya Hossain, Rosa Luxemburg, Virginia Woolf, Ding Ling, Simone Weil, and Emma Mashinini. To illustrate the breadth of interests of women political theorists, the selections highlight works ranging from the political poetry and fiction of Enheduanna, Sappho, Sor Juana, Phillis Wheatley, Tekahionwake, and Ding Ling, to the Dialogue of St. Catherine, Christine de Pizan's Book of the Body Politic, Wollstonecraft's Vindication of the Rights of Men, Tristan's The Workers' Union, Butler's Government by Police, Wells-Barnett's Southern Horrors, Hossain's Sultana's Dream, Weil's Reflections Concerning the Causes of Liberty and Social Oppression, and Mashinini's Strikes Have Followed Me All My Life. The broad-ranging texts included in the volume cross many boundaries of time, space, class, race, sex, culture, genre, and ideology. The book includes a general introduction by Berenice Carroll, biographical introductions by Carroll or Smith for each of the authors, suggested readings for individual authors, and a selected bibliography.